A fixed point theorem for a pair of maps satisfying a general contractive condition of integral type - P. Vijayaraju; B. E. Rhoades; R. Mohanraj (International Journal of Mathematics and Mathematical Sciences)
We give a general condition which enables one to easily establish fixed point theorems for a pair of maps satisfying a contractive inequality of integral type.